Analisis Perbandingan Pengaruh Media Pendingin Dromus dan Air Radiator Terhadap Kekasaran Permukaan Baja S45C Pada Proses CNC Miliing - Fatullah Faing; Eko Yudo; Zaldy Kurniawan (Jurnal Inovasi Teknologi Terapan, 2026)
This study aims to analyze the comparative effect of Dromus and radiator water cooling media on the surface roughness of S45C steel in the CNC Milling machining process. The quality of the machined surface is a critical indicator in the manufacturing industry, necessitating parameter optimization to achieve maximum efficiency. The Taguchi method with an L9 orthogonal array experimental design was used to evaluate the influence of three process parameters: spindle speed, depth of cut, and feed rate. Tests were conducted with three replications for each combination, and data were analyzed using the Signal-to-Noise (S/N) ratio calculation with the "smaller-is-better" category and ANOVA to determine the contribution of each factor. The results showed that Dromus cooling media consistently provided lower and more stable surface roughness values compared to radiator water. The optimal parameter combination found was a spindle speed of 1910 rpm, a depth of cut of 0.2 mm, and a feed rate of 330 mm/min. Contribution analysis revealed that when using Dromus, the depth of cut was the most dominant factor (63.40%), whereas with radiator water, spindle speed was the primary factor influencing surface roughness (45.67%).